Tradisi Pembacaan Surat Yasin dan AL-Mulk Kaum Ibu di Desa Sirambas Kec Panyabungan Barat Kab Mandailing Natal Sumatera Utara - Hasrul Fadli; Ahmad Deski; Yenni Rahman; Irpan Rambe (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The tradition of reciting Surah Yasin and Al-Mulk is routinely practiced by women in Sirambas Village. This is a form of worship performed in congregation to seek the blessings of Allah SWT. The focus of this study is the opening, main, and closing activities. The aim is to determine how the recitation of Surah Yasin and Al-Mulk is implemented in Sirambas Village, Panyabungan Barat District, Mandailing Natal Regency, North Sumatra. This study is a Living Qur'an-based field research study because it examines the community's response to the Qur'an in their lives. The practice of reciting Surah Yasin and Al-Mulk has been passed down through generations. This study used descriptive analysis. Data collection included interviews, observation, and documentation. The results of this study describe the tradition of reciting Surah Yasin and Al-Mulk among women in Sirambas Village, divided into three stages: the opening activity (preparation), the main activity (implementation), and the closing activity (prayer). This is done together and has been done for generations. By reading the Yasin and Al-Mulk surahs, the mothers feel many changes. Apart from their worship, the sisterhood of the mothers is also getting closer.